Two from the heart - Patterson, James, 1947-; Costantini, Frank; Raymond, Emily, 1972-; Sitts, Brian (New York : Little, Brown and Company, 2017)
In Tell Me Your Best Story After Anne McWilliams marriage ended and her home she realizes that her life has fallen out of focus. So she takes to the road to ask long lost friends and strangers a simple question: "What's your best story?" In Write Me a Life Tyler Bron runs a successful company but has no life. He hires a writer to write one from him. But will Tyler Bron be able to write the happy ending himself?
Tell me your best story / James Patterson and Emily Raymond -- Write me a life / James Patterson, Frank Costantini, and Brian Sitts.
Includes excerpt from "The 16th Seduction."
Keywords: Automobile travel -- Fiction; Interpersonal relations -- Fiction; Families -- Fiction